Proposal to study economic and environmental benefits of reducing soil erosion in Albania - Bockheim, James G.; Albania. Immovable Property Registration and Market Action Plan (Project). Project Management Unit. (Land Tenure Center, University of Wisconsin-Madison, 1997)
Soil erosion and associated nonpoint pollution are critical problems affecting the economic welfare, food security, and public health of Albania. Nearly 60 million tons of sediment are deposited by Albanian rivers into the Adriatic Sea each year. This translates into a national average soil erosion rate of 27.2 tons per hectare per year, which is more than twice the level of "tolerable" erosion established by many countries. This also means that an average of 2.3 mm of valuable topsoil are lost to the ocean each year. Accompanying the topsoil are agrochemicals such as pesticides and fertilizers as well as industrial pollutants, which are transported to reservoirs, rivers, lakes, and the ocean, thereby causing a degradation in water quality. The objectives of the proposed study include: to quantify the magnitude of soil erosion and its effects on water quality at three levels of intensity: site-specific, watershed, and the nation as a whole; to identify high-risk areas for immediate soil erosion control using a geographic information system; to create a public awareness program that uses soil erosion control as an example of land protection in Albania; to monitor the effectiveness of soil erosion control on discharge of sediments into the Adriatic Sea using remote sensing; and to determine the economic benefits of soil erosion control.
iii, 7 p.
Keywords: Soil conservation Environmental aspects Albania; Soil conservation Economic aspects Albania